Working memory and second language development: A complex, dynamic future? - Jackson, Daniel O. (Studies in Second Language Learning and Teaching, 2020)
Working memory (WM) is inherently dynamic and complex, being a multi-faceted system that links storage and processing components; yet it is widely understood as internal. Hence, in second language (L2) research, its connection to complex dynamic systems theory (CDST) remains underspecified. This paper seeks to bridge a gap between CDST and WM in L2 research. First, definitions of WM are reviewed, along with evidence for its relationship to L2 outcomes. Next, a brief overview of CDST highlights its metatheoretical and methodological implications. Three perspectives are presented to illustrate how WM can be viewed in terms of major tenets in CDST. These consider WM effects as: (1) context-dependent, (2) interrelated with those of other variables, and (3) amenable to change across the lifespan. Despite this reappraisal, numerous challenges remain. Thus, in addition to noting research opportunities, the paper also considers measurement issues, such as the determination of boundaries and selection of appropriate timescales. In closing, while WM studies have shown its influence on L2 proficiency and processing, to more fully understand its dynamic nature, what is needed is further research on the reciprocal influences of bilingual development and changes in WM components, such as control of attention.